Pelatihan Aplikasi Microsoft Office PowerPoint untuk Metode Pembelajaran - Wijana, Miki; Muhyidin, Yusuf; Wibowo, Asep (Ma'soem University, 2021)
The Miftahul Falah Ash-Shiddiqie Islamic Boarding School Education Foundation is located in the Rancaekek sub-district, Bandung regency. Is an educational institution in the field of Islamic religion. The teaching method used is still traditional by using writing instruments. Knowledge of computer science teachers is not yet smart. Computer lessons and training for Microsoft Office Power Point applications are carried out, able to provide benefits as a more modern and interesting learning medium. After implementing the Microsoft Power Point application computer training, teachers are expected to better understand the importance of technology as a learning medium.